(untitled) (Religious dialogue and cooperation, 2025)
Bosnia and Herzegovina is a country characterized by the interconnectedness of ethnic and religious affiliation, the country is home to three main ethnic groups (Serbs, Croats and Bosnians) who are members of three different religions (Orthodoxy, Catholicism and Islam). The history of Bosnia and Herzegovina is accompanied by deep religious and ethnic divisions and aspirations. The cause of conflict and intolerance in the country is often because of the different interest between all three religious parties. The intention of the authors of this paper is to draw attention to the importance of religious dialogue in interethnic relations in Bosnia and Herzegovina, as the main key for spreading a culture of peace, mutual tolerance and understanding.